Virtual connectedness in times of crisis: Chinese online art exhibitions during the COVID-19 pandemic. Issue 1 (2nd January 2022) - Snels, Jori
Abstract : When Chinese museums had to close their doors due to the outbreak of COVID-19, several online art exhibitions were created that were able to still create a sense of connectedness among their audience members during the pandemic. This article details three online exhibitions – by Chronus Art Center, by M WOODS, and by independent curator Yu Minhong – and explores how they communicate 'being-in-common' (a concept by Jean-Luc Nancy) in the online realm; it also proposes alternative forms of cosmopolitanism that do not rely on physical mobility. The exhibitions are analyzed using visual and discourse analysis and supported by semi-structured in-depth interviews with the curators. This study shows that a cosmopolitan art world does not need to rely on physical travel if connectedness is understood as being-in-common rather than meeting-in-person, digital technology is mobilized effectively, and cosmopolitanism is grounded in a re-localization. In an era when the global art world is looking for ways to reinvent itself and the mobility system on which it operates, the article contends that it would do well to look to and learn from the example of Chinese online exhibitions.